Draft Annual Plan 1984-85 Volume I Government of Uttar Pradesh - Planning Commission (Planning Commission, 1983)
Uttar Pradesh, with more than 16 per cent of population and nine per cent geographical area of the country, is. the most populous state. It is also one of the most economically backward states and needs much larger inflow of financial resources for its economic and social development as compared to the better developed states.
Government of Uttar Pradesh Planning Department